Social exchange of cigarettes by youth. Issue 2 (1st June 2003) - Forster, J; Chen, V; Blaine, T; Perry, C; Toomey, T
Abstract : Objective: This study seeks to determine the magnitude, nature, and correlates of social exchange of cigarettes among youth who smoke. Design: Cross sectional survey. Setting: Schools in 29 Minnesota communities. Participants: All students in grades 8, 9, and 10 (ages 13–16 years) in each participating school. The parent/child response rate for the survey was 90%. Analyses included 4124 respondents who smoked at least one cigarette in the month before the survey. Outcome measures: Social exchange scale, consisting of 16 items assessing aspects of social provision and acquisition of cigarettes. Results: Almost 90% of youth in this study had obtained a cigarette from, and about 75% of them had provided cigarettes to, another teen in the prior month. Daily smokers provided to more teens and provided more often than those who smoked less than daily. Daily smokers also reported having more social sources, both teens and adults, than lighter smokers, and were more likely to have both bought from and sold cigarettes to other teens (p < 0.0001 for all comparisons between daily and less than daily smokers). In a multivariate analysis, social exchange was associated with grade, whether siblings and friends smoke, level of smoking, age of smoking initiation, parental influences and community norms about teen smoking, and buying cigarettes. Conclusions: Social provision and acquisition of cigarettes among teens are widespread, reciprocal behaviours. Parental and community expectations about smoking influence social exchange, possibly by providing opportunities or barriers for social smoking. Commercial and social availability are not mutually exclusive; rather social exchange extends the reach of commercial sources.